The rights of God : Islam, human rights, and comparative ethics - Oh, Irene (Advancing human rights series., 2007)
Promoting Islam as a defender of human rights is laden with difficulties. Advocates of human rights will readily point out numerous humanitarian failures carried out in the name of Islam. In The Rights of God, Irene Oh looks at human rights and Islam as a religious issue rather than a political or legal one and draws on three revered Islamic scholars to offer a broad range of perspectives that challenge our assumptions about the role of religion in human rights. The theoretical shift from the conception of morality based in natural duty and law to one of rights has created tensions that hinder.